Correlation of the Main Parametres of Immun Systeminchildren with Localized Scleroderma by the Stages of the Disease - Mun Andrey1, Abdushukur Mannanov2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: In spite of significant development in modern medicine, the tendency of increase in thenumber of patients with localized scleroderma (LS) remaining actual with more severe clinical courses.Therefore, LS remains as one of the urgent problems of healthcare system. The etiology and pathogenesisof the disease is still unclear. Yet, LS frequently associates with deep and wide immune disorders andsubsequent complications.Materials and Method: We studied 45 children with LS, of whom 25 patients had a linear form, 16 hadplaque form, Pazini-Pieriniatrophodermia – in 2 participants, scleroatrophic lichen in 2. The control groupincluded 30 conditionally healthy children. We conducted monitoring of the cellular immunity system withimmunophenotyping using specific monoclonal antibodies to surface molecules CD3, CD4, CD8, CD16,CD20, CD25, CD54, CD95. Determination of the main classes of immunoglobulins in serum - IgG, IgA,IgM was also carried out.Results: There was a significant decrease in the number of T-helpers - CD4: at the stage of erythema andedema by 1.3 times, with sclerotic and atrophic - by 1.2 times. The content of cytotoxic CD8-lymphocytessignificantly decreased at the stages of erythema, edema and sclerotic on average by 19.4%. As a result ofmore significant inhibition of CD8, the CD4/CD8 ratio became larger (by 24%, 25%, and 11%, respectively,at the stage of erythema, sclerosis, and atrophy) than in the group of conditionally healthy patients. Patientswith LS, a statistically significant decrease in the serum percentage of total T-lymphocytes - CD3, and at thestage of erythema and atrophic edema it was 11.4%, and at the stage compaction - 6.3% compared with theparameters of control group.Conclusion: According to the level of inflammatory process with LS, immune dysfunctions are associatedwith a decline in the total amount of blood lymphocytes, namely CD4 T-helper cells and CD8 T-suppressors,CD54 endotheliocyte adhesion molecule, especially in the stages of erythema and edema or sclerosis.Learning these parameters may help to assess the immunological changes, and can be informative for thedetermination of the course, prognosis and further treatment.